Fetal brain biometry and cortical development in congenital heart disease: A prospective cross sectional study. Issue 1 (7th September 2022) - Rizzo, Giuseppe; Pietrolucci, Maria Elena; De Vito, Marika; Pavjola, Maqina; Capponi, Alessandra; Mappa, Ilenia
Abstract: Objective: To evaluate brain biometry and cortical development by neurosonography in fetuses with congenital heart defect (CHD) and evaluate differences among different type of CHD. Methods: In a prospective cross sectional study singleton fetus with CHD were matched with controls and grouped into two categories according to the predicted severity of cerebral arterial oxygen deficit induced by the CHD: Group A mildly reduced or normal and Group B moderately to severely reduced. Neurosonography was done at 30–33 weeks to obtain measurements of corpus callosum (CC), cerebellar vermis (CV), Sylvian fissure (SF) insula, parieto‐occipital fissure (POF), and calcarine sulci fissures (CSF). All the neurosonographic parameters were adjusted by head circumference (HC). Results: A total of 78 fetuses with CHD (group A 30; group B 48) and 80 matched controls form uncomplicated pregnancies were considered. CHD fetuses have significantly smaller CC, CV, SF, and POF and bigger insula when compared to control fetuses. These differences are more marked in group B fetuses. These differences remained significant after correction for HC values. Conclusion: Fetuses with CHD have an impaired cortical development and these variations are more evident in those with a predicted lower oxygen delivery to the brain. Abstract : This study provides evidence that fetuses with isolated congenital heart defect (CHD) have a smaller corpus callosum and cerebellar vermis and an impaired cortical development compared with normal controls at 30–33 weeks' gestation, with a more prominent reduction in the CHD subgroup with expected poorer oxygen supply to the fetal brain.